Deficit Irrigation Strategies in Vitis vinifera L. cv. Cannonau under Mediterranean Climate. Part I - Physiological Responses, Growth, Yield and Berry Composition - Fernandes de Oliveira, A.; Mameli, M.G.; de Pau, L.; Satta, D.; Nieddu, G. (South African Journal of Enology and Viticulture, 2016)
The effect of deficit irrigation strategies on physiological performance, growth, source:sink balance, water productivity and berry composition of field-grown grapevines of Vitis vinifera L. cv. Cannonau (syn. Grenache)/1103P were investigated in Sardinia, Italy, in 2009. In two of the treatments, both sides of the root system received 50% and 25% crop evapotranspiration (ETc), referred to as strategies DI50 and DI25, respectively. In the third treatment, which included partial root-zone drying (strategy PRD), ETc was set at 50%. All three treatments were compared to a full irrigation control (strategy FI), thus 100% ETc. No severe water stress was imposed from berry development onwards. Strategies DI25 and PRD induced higher stomatal closure and leaf water-use efficiency. A slightly higher net assimilation rate was recorded in FI before véraison. During ripening, leaf area decreased in DI50 and DI25, but lateral shoots continued to grow in FI and PRD. Yield and pruning weight were higher in FI, but in all the treatments the vines were source:sink balanced and supported ripening. Irrigation water productivity was higher in DI25, and no significant differences in yield or water productivity were observed between PRD and DI50 irrigated with a similar volume of water. Full irrigation produced berries with a significantly higher fresh and dry weight, lower °Brix and higher malic acid at harvest, while PRD berries weighed less and had less titratable acidity, lower phenol content and a higher pH. Total anthocyanin contents were consistently lower in DI25 and PRD, with highest values measured in DI50. The treatments showed different anthocyanin profiles, with a higher concentration of acylated anthocyanin in DI25 and PRD.